INVESTIGATION THE INFLUENCE OF ELECTRON BEAM PARAMETERS ON THE CATHODOLUMINESCENCE OF CADMIUM TELLURIDE. (Journal of Sciences & Technology, 2018)
The cathodoluminescence signal (Cl) has been investigated theoretically for p-type CdTe, in order to understand the effect of incident electron beam parameters (energy Eo, intensity Ip), at low injection level, on the excess carriers, the cathodoluminescence intensity (ICl) and the depletion region (Zd). To do this a self-consistent calculation method of (ICl) has been used.The obtained results show that the excess concentrations of carriers have a maximum value near the surface and decrease when E0 increases. Regarding the depletion region we observe a decrease of the depth as a function of Ip for the relatively great values and an increase with increasing Eo. The curves ICl = f(E0) show a maximum in the energy interval of [30-40 keV] and a rapid decrease for high values of Ip. Additionally, we observe, in general, an increase of ICl with increasing Ip. Finally, we record a linear variation of the intensity Cl as a function of Ip, according to different energies E0.